Correlation Analysis Between Material Thickness and Welding Length on The Completion Time of Vessel Product in The Static Mixer Project - Bahri, Salsabila; Hayati, Nahrul (JURNAL SINTAK, 2026)
This study aims to analyze the relationship between fabrication technical parameters (material thickness and welding length) and the completion time of static mixer vessel products. The research sample consisted of 30 product units, with data collected retrospectively from the project documentation of PT. NOV Profab for the period December 2024 until July 2025. The method used was quantitative correlational. The Shapiro-Wilk normality test indicated that the data was not normally distributed (p < 0.05), therefore correlation analysis was performed using the non parametric Spearman’s Rank test. The results show that the relationship between material thickness and completion time is very weak and not significant (r = 0.126 and p = 0.507). Similarly, the relationship between welding length and completion time is weak and not significant (r = 0.301 and p = 0.106). In conclusion, material thickness and welding length are not proven to have a statistically significant relationship with the completion duration of static mixer products. This finding implies that project time estimation requires consideration of factors other that these technical parameters.